2020
DOI: 10.1007/s42235-020-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Deposits on Microstructured Surfaces

Abstract: Research into evaporating droplets on patterned surfaces has grown exponentially, since the capacity to control droplet morphology has proven to have significant technological utility in emerging areas of fundamental research and industrial applications. Here, we incorporate two interest domains-complex wetting patterns of droplets on structured surfaces and the ubiquitous coffee-ring phenomenon of nanofluids containing dispersed aluminium oxide particles. We lay out the surface design criteria by quantifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 75 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…This work expands on earlier works where one single microstructure configuration 27 , cavities instead of pillars 51 , limited binary mixture concentrations (0% and 30%) on a single micro-pyramid structured configuration 38 or pure fluids varying in surface tension 41,44 . We note that single structure configuration as in 27 and 38 or the use of pure fluids 38,44,45 did not allow for the wide range of interactions and the regime map further extended and proposed in this work, of eventual concern to wider range of applications and communities. Future work suggests adopting other experimental techniques and characterisation such as internal total reflection 64 and electrochemical impedance 65 as well as other binary mixtures 66 to better elucidate the intimate interactions between the wide ranges of surface tension fluids and solid structures presented in this work.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This work expands on earlier works where one single microstructure configuration 27 , cavities instead of pillars 51 , limited binary mixture concentrations (0% and 30%) on a single micro-pyramid structured configuration 38 or pure fluids varying in surface tension 41,44 . We note that single structure configuration as in 27 and 38 or the use of pure fluids 38,44,45 did not allow for the wide range of interactions and the regime map further extended and proposed in this work, of eventual concern to wider range of applications and communities. Future work suggests adopting other experimental techniques and characterisation such as internal total reflection 64 and electrochemical impedance 65 as well as other binary mixtures 66 to better elucidate the intimate interactions between the wide ranges of surface tension fluids and solid structures presented in this work.…”
Section: Discussionmentioning
confidence: 88%
“…Two contact angles were reported depending on the azimuthal direction of the droplet and the observation. Moreover, geometrical shapes for pure water have also been found in the work of spacings between pillars on a hydrophobic coated pillared surface 45 . The study showed that varying the spacing between pillars and the shape of the pillars, the shape of the droplets for the low surface tension fluids could be controlled, which eventually dictated the final shape and distribution of the deposits 45 .…”
Section: Introductionmentioning
confidence: 90%
“…Although there have been a number of studies concerning the physics involved in the edge effect 19,24 and the evaporation characteristics of pinned asymmetric drops, 25–27 the contact line deposition has not yet been fully investigated for them. 23,28…”
Section: Introductionmentioning
confidence: 99%
“…These depend on atmospheric conditions like temperature , and humidity . Furthermore, external factors, such as the characteristics of the substrate like surface wettability, , adhesive nature, texture, , and viscoelastic nature are critically important. These factors and the interplay between them play a key role in influencing the thermodynamic interactions and processes that govern the mass transport that, ultimately, determines the final morphology of the solid matter.…”
Section: Introductionmentioning
confidence: 99%